CRIMINOLOGICAL REVIEW OF THE CRIME OF DIFFERENCE IN EFFORTS TO PROTECT CHILDREN WHO ARE OBJECTED BY CRIME - Iyam Irahatmi Kaharu; Fahria Fahria; Muhammad Mufti M Djafar (Faculty of Law, Khairun University, 2021)
Crime is a very anti-social act that consciously gets a reaction from the state in the form of giving suffering (punishment or action). Crime as a behavior is an act of deviance, is against the law or violates statutory regulations and is detrimental to the community in terms of decency, decency and order of community members. Crime can be defined juridically and sociologically. Crime is part of people's lives and is an everyday event. A philosopher named Cicero said Ubi Societas, Ibi Ius, Ibi Crime which means there is a society, there is law and there is crime. The benefit of studying criminology is that criminology contributes to the formulation of new legislation (the Criminalization Process), explaining the causes of crime (Criminal Ethylogy) which in turn creates efforts to prevent crime. Another issue regulated in the child protection law is how to punish adults who commit crimes against children and also the responsibility of parents, society and the state in protecting children. This research was conducted in North Maluku, precisely in the city of Ternate. This research will use a descriptive type of analysis with a qualitative approach. In collecting data through library research, field studies and documentation studies